Filariasis Diagnosed by Real Time Sonographic Imaging as Filarial Dance Sign: A Case Report - Shrestha, Sumiran; Shrestha, R.; Gokhale, S. (Nepal Medical College Journal, 2019)
Lymphatic filariasis is a major public health problem. World Health Organization (WHO) has graded filariasis, as the second leading cause for permanent and long-term disability after leprosy. It is a chronic disabling parasitic disease prevalent in South Asia and Africa. A case of 26-year-old male resident of district Palpa presented with swelling of left inguinal region since 3-4 days and pain in inguinal region since a month. He had no history of trauma, fever or any other systemic symptoms. High frequency, high-resolution scrotal ultrasonography is a valuable technique for diagnosing scrotal filarial infection. This method revealed “Filarial Dance Sign” which is a distinctive and continuous pattern of movement of live microfilaria indicating active infection. It is a simple, rapid, sensitive and noninvasive technique. Noninvasive ultrasonography is preferable to the invasive FNAC.